Postgraduate education of dentists in Poland - current state and perspectives - Justyna Grudziąż-Sękowska; Janusz Kocik; Magdalena Kapica; Sara Shamsa; Magda Mazurek; Małgorzata Wywrot; Urszula Religioni; Jarosław Pinkas; Wojciech Stefan Zgliczyński (Wiedza Medyczna, 2022)
Introduction: In the Polish medical education system, dentists, after graduating from university studies, obtain the right to practice their profession with the possibility of continuing their education. One of the forms of postgraduate development is specialist training. In the face of dynamic demographic, economic and social changes taking place in Polish society, the availability of an appropriate number of qualified specialists is a guarantee of health safety. Conducting reliable analyzes allows to set the right directions for the development of specialization education and its adaptation to changing health needs.Aim of the article: The aim of the study was a quantitative analysis and evaluation of changes taking place in the system of specialist education of dentists in treatment specializations in the years 2010-2020.Material and methods: The analysis included the data from the register of doctors undergoing specialization training; register of entities authorized to conduct this training, kept by the Centre of Postgraduate Medical Education of Warsaw(CMKP); data of the Medical Examinations Center on the number of dentists taking the specialization examination and on the number of diplomas issued and the passing rate of the National Specialization Examination. The material analysis was quantitative.Results: The analysis of data register about dentists undergoing postgraduate training shows that in 2010-2020 there was a gradual increase in the number of entities offering dental specializations and the number of training places they provide, including residential places. These changes were accompanied by an increase in the number of dentists receiving specialist training more by 50% (52,3%) in 2020 in comparison to 2010 . The situation differed between the seven analyzed specializations: conservative dentistry with endodontics, pediatric dentistry, orthodontics, dental surgery, periodontics, dental prosthetics and maxillofacial surgery.Conclusions: The changes that took place in the system of specialization education of dentists in 2010-2020 included an increase in the number of dentists undergoing training, an increase in the percentage of people undergoing specialization as part of the residency, an increase in the number of entities conducting specialization, and thus increasing the availability of training places.